การประเมินความสัมพันธ์ทางพันธุกรรมและการจำแนกข้าวปลูกบางพันธุ์ด้วยเครื่องหมายสก๊อต - สิงห์ศิลารักษ์ ทัศนีย์; เจียมเจือจันทร์ จุฑามาศ; ขุนปักษี เปรมณัช; ธนานันต์ ธีระชัย; ธนานันต์ นฤมล (Thai Journal of Science and Technology, 2017)
บทคัดย่อ ข้าวเป็นพืชอาหารหลักที่สำคัญชนิดหนึ่งของโลก ประชากรในประเทศแถบภูมิภาคเอเชียนิยมบริโภคข้าวเป็นอาหารหลักมากกว่าภูมิภาคอื่น ๆ ส่งผลให้อัตราการผลิตข้าวของประเทศไทยเพิ่มสูงมากขึ้น งานวิจัยนี้จึงใช้เครื่องหมายสก๊อตมาจำแนกพันธุ์ข้าวปลูก จำนวน 24 พันธุ์ โดยใช้ไพรเมอร์ 80 ชนิด พบว่าไพรเมอร์ 50 ชนิด สามารถเพิ่มปริมาณดีเอ็นเอได้ เมื่อคัดเลือกไพรเมอร์ 22 ชนิด ที่ให้ลายพิมพ์ดีเอ็นเออย่างชัดเจนมาตรวจสอบกับดีเอ็นเอข้าวแต่ละพันธุ์ พบว่าสามารถแยกความแตกต่างระหว่างพันธุ์ได้ด้วยแถบดีเอ็นเอจำเพาะกับพันธุ์ นอกจากนั้นยังพบไพรเมอร์ที่สามารถจำแนกพันธุ์ข้าวทั้ง 24 พันธุ์ ด้วยการใช้ไพรเมอร์เพียงชนิดเดียว เมื่อวิเคราะห์ลายพิมพ์ดีเอ็นเอด้วยโปรแกรม NTSYS พบว่าสามารถจำแนกพันธุ์ข้าวออกเป็น 3 กลุ่ม และเมื่อวิเคราะห์ความสัมพันธ์ทางพันธุกรรมพบว่ามีค่าสัมประสิทธิ์ความเหมือนอยู่ระหว่าง 0.60 ถึง 0.91 โดยงานวิจัยนี้แสดงให้เห็นว่าเครื่องหมายสก๊อตมีศักยภาพในการจำแนกและตรวจสอบพันธุ์ข้าว คำสำคัญ : ข้าว; เครื่องหมายสก๊อต; ความสัมพันธ์ทางพันธุกรรม; การจำแนก; เครื่องหมายดีเอ็นเอ Abstract Rice is the major worldwide food crop species. As being a rice-staple food country, like other Asian countries, there is a higher rate of rice production in Thailand. In this work, the start codon targeted (SCoT) markers were used to identify 24 rice cultivars from farmers. Eighty SCoT primers were screened and 50 primers could be used for DNA amplification. Twenty-two SCoT primers with clear amplified products were selected and used to analyze all cultivars. The result showed differences among 24 rice cultivars with specific DNA bands. In addition, some of 22 SCoT primers were able to identify each rice cultivar using only one primer. All of the DNA fingerprinting was analyzed base on polymorphic bands by the NTSYS-pc program, by which the samples could be classified into 3 groups. A dendrogram based on polymorphic bands showed genetic similarities among rice cultivars with similarity coefficients in a range of 0.60-0.91. This research shows that the SCoT markers have a potential for detection the rice cultivars. Keywords: rice (Oryza sativa L.); SCoT marker; genetic relationship; identification; DNA marker